Perkembangan Lembaga Pendidikan Non Formal Rumah Tahfiz di Kota Medan - Asari, Hasan; Arsyad, Junaidi; Hidayati, Nur (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to analyze: The institutional elements of Tahfiz houses in Medan, the learning system implemented at Tahfiz Houses in Medan, operational financing at Tahfiz houses in Medan, supporting and inhibiting factors for Tahfiz houses in Medan. The research method used can be categorized as field research, namely research that aims to collect data and information from various observations in the field. The research approach used in this research is a phenomenological approach. The results of the research show that: 1) The educational institutional elements in the five Tahfiz houses in this study have been fulfilled, including: the existence of buildings, educators and students in each Tahfiz house institution, 2) The learning system implemented in the Tahfiz House in Medan has different systems. The system implemented in the learning process is determined by the management of the institution. 3) Operational financing at Rumah Tahfiz in the city of Medan, it was found that in terms of financing, some were handled by individuals, some were handled by groups. no funding was found that was specifically managed by the government, 4) Supporting factors in the development of the Tahfidz House in Medan City, including: adequate infrastructure, strategic location of the tahfiz house, and the presence of donors. The inhibiting factors include: Weak tumah tahfiz management, less active role of teachers, lazy nature of students, and lack of parental support.